2016
DOI: 10.1111/neup.12303
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese familial ALS patient with autonomic failure and a p.Cys146Arg mutation in the gene for SOD1 (SOD1)

Abstract: We describe a Japanese man with familial amyotrophic lateral sclerosis (ALS) associated with a p.Cys146Arg mutation in the copper/zinc superoxide dismutase gene (SOD1). The patient developed bulbar signs followed by rapidly progressive limb muscle weakness. The prominent clinical feature was orthostatic hypotension due to autonomic failure, which occurred after he underwent tracheostomy 1 year and 3 months after the onset. Thereafter, he required mechanical ventilation and progressed to communication stage V (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
4
18
0
1
Order By: Relevance
“…Importantly, as seen in the present autopsy case, cases of FALS with an I113T SOD1 gene mutation consistently manifested CIs in the absence of LBHIs, except for one case in which only a small number of LBHIs were also encountered . It is also noteworthy that the occurrence of CIs in the absence of LBHIs has been reported in a case of FALS with an C146R SOD1 gene mutation …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Importantly, as seen in the present autopsy case, cases of FALS with an I113T SOD1 gene mutation consistently manifested CIs in the absence of LBHIs, except for one case in which only a small number of LBHIs were also encountered . It is also noteworthy that the occurrence of CIs in the absence of LBHIs has been reported in a case of FALS with an C146R SOD1 gene mutation …”
Section: Discussionsupporting
confidence: 79%
“…A review of the literature confirmed that most autopsied FALS patients with SOD1 gene mutations showed degeneration in Clarke's nucleus, the posterior spinocerebellar tract and dorsal columns, with a variety of combinations of the degenerative lesions and their extent (Supplementary Table). Observation of affected siblings suggested that protracted disease duration was related to development of more severe and more widespread degenerative lesions, which might have been the case in the present autopsied patient who survived 11 years with the support of artificial ventilation for the final 5 years before death.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In that report, neuropathological analysis demonstrated degeneration of the pontine nuclei, dentate nuclei and Purkinje cells in the cerebellum, in addition to the neuropathological features associated with cases of posterior‐column‐type ALS1 . The presence of inferior olivary hypertrophy is noteworthy in our case, as it is rare in both sporadic and familial ALS cases . The hypertrophy of the inferior olive nucleus was accompanied by pNF‐positive inclusions, but not SOD1‐positive inclusions, and appeared “isolated” as we did not observe degeneration of the red nucleus, dentate nucleus, or central tegmental tract.…”
Section: Discussionsupporting
confidence: 60%
“…Voiding difficulty is partly attributed to weakness of the pelvic or abdominal wall muscles, but a neurogenic mechanism may contribute to bladder dysfunction with disease progression. Some patients with superoxide dismutase‐1 gene variants have a neurogenic or atonic bladder . All of these signs may have an association with ALS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%